Binary and ternary pyrotechnic systems containing manganese, molybdenum, barium peroxide and strontium peroxide - Drennan, Robin Lennox (Rhodes University, Faculty of Science, Department of Chemistry, 1991)
Barium peroxide was selected as oxidant in a fundamental physico-chemical study of binary pyrotechnic systems on account of its apparently simple decomposition stoichiometry. With this selection, the choice of fuel was governed by the requirements of a self-sustaining reaction at combustion temperatures below the melting point of the platinum/rhodium thermocouples (âˆ¼1760Â°C) used for recording temperature-time profiles during burning, and at burning rates not exceeding the response of the sensors used to monitor combustion. Both manganese and molybdenum metal powders satisfied the above requirements. Strontium peroxide was also available as an oxidant and so the combustion of binary metal/oxidant systems using both fuels and both BaOâ‚‚ and SrOâ‚‚ oxidants was investigated. The Mn/BaOâ‚‚, MoBaOâ‚‚ and Mn/SrOâ‚‚ systems burnt over a wide range of compositions, but the range of ignitable compositions for the Mo/SrOâ‚‚ system was very limited. The linear burning rates, for all these systems, ranged from 2 to 12 mm sâ »Â¹ and burning rates were increased by the use of smaller particle-sizes of fuel and greater loading pressures. Inert additives generally decreased the burning rate. Temperature-time profiles were recorded for all the compositions which sustained combustion. Kinetic parameters were estimated from the shapes of these profiles using procedures developed by Hill et al and Boddington and Laye. Activation energies derived from the profiles were low (3 to 40 kJ molâ »Â¹) and support suggestions that reactions at high temperatures are controlled by diffusion processes. Thermal analysis was used to identify the processes occurring in the four systems. The main exothermic events were observed to correspond approximately with the onset of oxidant decomposition. A pre-ignition reaction was tentatively identified in the Mn/BaOâ‚‚ system. Oxidation of the metal fuels was generally incomplete, probably because of the formation of protective layers of product. Activation energies, derived from thermal analysis results, were in the range of from 70 to 720 kJ molâ »Â¹. Ternary systems containing either mixed fuels or mixed oxidants were also examined. No interactions hetween the fuels or between the oxidants were observed. Other techniques used included bomb calorimetry, measurement of thermal conductivity, X-ray powder diffraction, infrared spectroscopy and scanning electron microscopy.
Keywords: Thermochemistry -- Research; Thermal analysis -- Research; Chemistry, Analytic -- Research; Manganese; Molybdenum